FAKTOR-FAKTOR YANG MEMPENGARUHI KELEMAHAN PENGENDALIAN INTERN PEMERINTAH DAERAH - Agustina, Gita Putri; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of environment control, risk measurement, control activity, information and communication also the monitoring to the weaknesses of internal control of government on the section in the local apparatus work unit (SKPD) of Surabaya city. The population is all employees of financial management in 30 the local apparatus work units (SKPD) in Surabaya city. The sample collection technique has been done by using purposive sampling. The analysis technique has been done by performing the multiple linear regressions analysis. The result of this research shows that the control environment has negative influence to the weaknesses of internal control of the government, risk measurement does not have any influence to the weaknesses of internal control of the government, and internal activity has positive influence to the weaknesses of internal control of the government, information and communication has negative influence to the weaknesses of internal control of the government as well as the monitoring does not have any influence to the weaknesses of internal control of the government on SKPD city of Surabaya.Keywords: Environment Control, Risk Measurement, Control Activity, Information and Communication, The Weaknesses of Internal Control.